Wschowa w obliczu galopującego postępu usług bibliotecznych = Wschowa in the Face of Rapidly Advancing Library Services - Kamińska, Kamila (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article illustrates the modernization process of the Public Library of the Town and Municipality of Wschowa and the development of the library services it provides. It presents a wide range of cultural events organized by the Wschowa library since its relocation. The author discusses the role of the modern librarian and the changing perception of the essence of their work.
Keywords: biblioteka; modernizacja; rozwój usług; rola bibliotekarza; library; modernization; service development; role of the librarian